Appeals of Afghanistan during war of 1979-1989: view of the soviet soldier - Dmytro Ostrovyk (Cхід, 2018)
In the article, on the basis of verbal evidences of soldiers who fought in Afghanistan, sources of personal origin and different literature, was made an attempt to show the socio-cultural space of Afghanistan during the war on years 1979-1989 through the perception of Soviet soldiers. The socio-economic situation of the local population was observed, indicating significant property differentiation. This gave reason to both there searchers and the soldiers of the Afghanistan war to talk about the anachronisms of the "feudal" system in the country. It was specified on a number of management problems in a war, about which our respondents spoke and researchers wrote. In particular, the negative phenomenon was the desertion of the local population from the ranks of the army, sale of state property, and even worse cases - transition to the side of illegal armed groups. The existence of different "tactics of treatment" of the local population with the Soviet soldiers was proved. It was established that the dominant components of the attitude of Afghans to the military contingent of the Soviet troops in Afghanistan were as "national-ethnic", economic, as well as religious affiliation of the Afghan society. The attitude towards the Soviet forces in the investigated period was also viewed through the property situation of the local population, when the imp over is heed residents, being socially unprotected, found support among the Soviet military. At the sometime, due to the struggle, often armed, between different clans and tribes, oil legal armed formations for spheres of influence, there was cooperation of some of them with the official ruling regime and, accordingly, Soviet forces.